Oral Presentations 2019
DOI: 10.1136/annrheumdis-2019-eular.5727
|View full text |Cite
|
Sign up to set email alerts
|

Op0106 a Novel Knock-in Mouse Model of Caps That Develops Amyloidosis: Therapeutic Efficacy of Proton Pump Inhibitors

Abstract: BackgroundCryopyrin associated periodic syndromes (CAPS) are a group of autoinflammatory diseases linked to gain-of-function mutations in the NLRP3 gene that cause uncontrolled IL-1β secretion. CINCA syndrome is the most severe CAPS disease characterized by central nervous system disabilities with a long-term risk of secondary amyloidosis.Proton pump inhibitors (PPIs), commonly used as inhibitors of gastric acid production, also display anti-inflammatory properties, making them promising drugs in sepsis and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A previous study has reported that Nlrp3 mutation caused amyloid deposits and inflammatory infiltrates in spleen. 29 Also, the Nlrp3's reads per kilobase per million mapped reads (RPKM) of spleen is highest among the organs in adult mice (NCBI, Mouse ENCODE transcriptome data). Thus, we explored whether ATZ could induce the activation of Nlrp3 in spleen.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has reported that Nlrp3 mutation caused amyloid deposits and inflammatory infiltrates in spleen. 29 Also, the Nlrp3's reads per kilobase per million mapped reads (RPKM) of spleen is highest among the organs in adult mice (NCBI, Mouse ENCODE transcriptome data). Thus, we explored whether ATZ could induce the activation of Nlrp3 in spleen.…”
Section: Introductionmentioning
confidence: 99%